A novel practical preparation of methyl methanethiosulfonate from dimethyl sulfoxide initiated by a catalytic amount of (COCl)2 or anhydrous HCl. (2nd November 2021) - Huang, Shuai; Wang, Hao; Liu, Yongguo; Sun, Baoguo; Tian, Hongyu; Liang, Sen
Abstract : A novel practical preparation method for methyl methanethiosulfonate (MMTS) has been developed. Dimethyl sulfoxide was converted to MMTS in the presence of a catalytic amount of oxalyl chloride or anhydrous HCl in acetonitrile under reflux in an ideal yield. Methanesulfenic acid was proposed to be the key intermediate for the formation of MMTS. GRAPHICAL ABSTRACT: UF0001